Xenogenic Implantation of Equine Synovial Fluid-Derived Mesenchymal Stem Cells Leads to Articular Cartilage Regeneration - Mohammed Zayed; Steven Newby; Nabil Misk; Robert Donnell; Madhu Dhar (Stem Cells International)
Horses are widely used as large animal preclinical models for cartilage repair studies, and hence, there is an interest in using equine synovial fluid-derived mesenchymal stem cells (SFMSCs) in research and clinical applications. Since, we have previously reported that similar to bone marrow-derived MSCs (BMMSCs), SFMSCs may also exhibit donor-to-donor variations in their stem cell properties; the current study was carried out as a proof-of-concept study, to compare the in vivo potential of equine BMMSCs and SFMSCs in articular cartilage repair. MSCs from these two sources were isolated from the same equine donor. In vitro analyses confirmed a significant increase in COMP expression in SFMSCs at day 14. The cells were then encapsulated in neutral agarose scaffold constructs and were implanted into two mm diameter full-thickness articular cartilage defect in trochlear grooves of the rat femur. MSCs were fluorescently labeled, and one week after treatment, the knee joints were evaluated for the presence of MSCs to the injured site and at 12 weeks were evaluated macroscopically, histologically, and then by immunofluorescence for healing of the defect. The macroscopic and histological evaluations showed better healing of the articular cartilage in the MSCs’ treated knee than in the control. Interestingly, SFMSC-treated knees showed a significantly higher Col II expression, suggesting the presence of hyaline cartilage in the healed defect. Data suggests that equine SFMSCs may be a viable option for treating osteochondral defects; however, their stem cell properties require prior testing before application.